KEANEKARAGAMAN JENIS (SPECIES) TUMBUHAN PAKU (PTERIDOPHYTA) DI AREA KAMPUS UPR PALANGKA RAYA (The Pterydohpyta diversity in campus of UPR area Palangka Raya): Agus Sadono - Administrator Journal (HUTAN TROPIKA, 2018)
ABSTRACTCampus UPR areas in central Kalimantan has a diverse community of Pteridophyta. Thediversity of Pteridophyta species or ferns is one of floral potentials that are not being awared bymost people due to the lack of the data and information on species diversity and utilization.These kinds of species were believed to spread widely in Indonesia regions. Ferns are uniqueand have potential use, such as materials for feed, medicinal or ornamental plants. The studyaimed to obtain reliable data and information about fern diversity as well as their traditionalutilization performed mainly by people living around the campus UPR area. The research wasconducted through exploration method by collecting many fern species that were found incampus UPR area. The species identification was using descriptive analytical methods. Theobtained data were presented in the forms of tabels .. Results showed that there were 35fern species consisting of 17 families. The types that were mostly found came fromPolypodiaceae familiy (8 species). Based on the potential utilization, those which can be usedas ornamental plants were Asplenium pellucidum. Lam., and Dipteris conjugata Reinw.Elevenspecies from Lecanopteris carnosa (Reinw.) Blume. and Selaginella Plana (Desv.ex Poir)Hieron. were used for medicinal herbs. One species, Gleichenia hispida Mett.ex Kuhn. can beused for handycraft material, while other 3 species from Pteris mertensioides Willd andDiplazium accendens Blume can be used for food material.Keywords: Ferns, Pteridhopyta, Campus UPR areas, diversity.